The Managerial Transformation of Italian Co-operative Enterprises 1946-2010 - Patrizia Battilani; Vera Zamagni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
The Italian co-operative enterprises have prospered in the last thirty years in various sectors. In this essay we analyze the role played by managerilization in allowing Italian co-ops to compete nationally and internationally with capitalist enterprises. On the basis of a substantial set of company histories and managers interviews, we have built a three generations model of co-ops managers, which shows the changes that have allowed co-ops to become fully equipped with managerial skills. The strong leadership of umbrella organizations, the inner careers of most managers and legislation have been instrumental in avoiding demutualization, the killer of co-ops in many other countries.
Keywords: N80; 330